Pendekatan Baharu al-Shaykh ‘Abd Allah al-Ghadamsi dan al-Imam Muhammad ‘Abduh dalam Memajukan Masyarakat Islam - Yusoff, AM; Said, NLM; Amiruddin Mohd Sobali (Penerbit Univ Kebangsaan Malaysia, 2024)
Al-Shaykh 'Abd Allah al-Ghadamsi is one of the figures who were contributing a lot in the history of the rise of Muslim community in Malaya. His presence in Malaya was on the request of figures and local Islamic activists to lead the mission to progress Islamic society in this region and release them from ignorance, retrogression and weakness. In parallel with the rise of global Muslim societies who commonly were under the colonial control especially in Middle East, which considered as the centre of the rise of Islam, the leaders' presence from there was cordially welcomed. Nevertheless, this mission was not an easy duty. So as to realise this noble dream, there were so many challenges and obstacles from external and internal parties had been faced. Through the study on the approach brought by this scholar and the response from his contemporary style, it seems like the history of struggle of a scholars' emergence and modern Islamic activist pioneering figure named al-Imam Muhammad 'Abduh, in several ways. Comparatively, this study aims the approach applied by these two scholars to develop the Muslim community in their places, its reaction which was received because of that approach, and the method used to overcome the challenges based on their wisdom and grit for the sake of the struggle contiunity. This qualitative research is formed by data collection from various sources and analysed to respond related issues following the framework has been decided. The findings of this important research are the similarities in approaches and responses which leave the deep impact into the continuity their legacy to the next age.